Differences and relationships between talent detection, identification, development and selection in sport: A systematic review - Zhao, Jie; Xiang, Changqing; Kamalden, Tengku Fadilah Tengku; Dong, Wenting; Luo, Hua; Ismail, Normala (Elsevier, 2024)
Although there are numerous studies on talent, especially talent identification, development, and selection, both on influencing factors and model construction or talent prediction, they have relatively independently explored some of its stages. Undeniably, talent development is continuous and phased, with specific tasks to be completed at each step, and these steps have certain differences and relationships. The aim of this review is to provide a clear distinction between the entire talent cultivation process, with the purpose of having better methods and measures for each stage to minimize the turnover rate and ensure the integrity of the talent development process. Through searching the Web of Science ™ database, this review was performed according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Selected were original articles in English containing data or models related to talent detection/ identification/development/selection in sports. A total of 16 articles were included in the study by reviewing the literature. This overview presents the differences and relationships between the four stages of talent cultivation, where these different aspects are aim, purpose, approach, and emphasis. The relationship is characterized by continuity, progressive, complementary, and mutually. This finding shows that each stage is not developed independently, but is an integral part of the talent training process. Additionally, better differentiation and strengthening of the links between the various talent cultivation stages are considered to contribute to elite athlete development. This review highlights the differences and relationships that exist at each stage of talent cultivation. Meanwhile, some measures are also proposed to strengthen the connection of these phases and how to reduce the turnover rate of talent, which can provide theoretical references for coaches or stakeholders. Based on the results of the review, it is also recommended that future research on talent cultivation could take into account the intrinsic linkages between the various stages and develop talent training programs in a multidimensional way.